Use of the portage curriculum to impact child and parent outcome in an early intervention program in Lebanon - Sarouphim, Ketty M. (2020)
The purpose of this study, that took place in Lebanon, is to investigate the effectiveness of Portage, a home-based early intervention program for children with special needs. The sample consisted of 16 children (eight male and eight female) whose ages ranged between 1 and 3 years. Participants were provided with home-based services by a Portage home-visitor for a period of six months. Data were collected before and after the intervention. Participants’ progress was evaluated in five developmental areas: communication, social-emotional, exploration, purposeful-motor activity, and sensory organization. Parents’ satisfaction with the program’s provisions was also examined. The results revealed significant differences in the participants’ pre and post ratings, indicating improvement in the children’s functional skills in all developmental areas. Also, parents’ interviews revealed satisfaction with the program’s services. In sum, Portage seems to be a promising home-based intervention, but further research is needed before making any claims about its wider potential.